Effects of the Good Behavior Game on Challenging Behaviors in School Settings. (December 2014) - Flower, Andrea; McKenna, John W.; Bunuan, Rommel L.; Muething, Colin S.; Vega, Ramon
Challenging behavior at school remains a concern for teachers and administrators. Thus classroom management practices to prevent challenging behavior are sorely needed. The Good Behavior Game (GBG) has been found to be useful to positively change student behavior. However, previous reviews of the GBG have not quantified effects, have not focused solely on school and classroom behaviors, and have not examined study features that facilitate greater outcomes. Twenty-two peer-reviewed journal articles were reviewed. Study data were analyzed using effect sizes, percent of nonoverlapping data, percent of all nonoverlapping data, and hierarchical linear modeling to determine intervention effectiveness as well as study features that facilitated greater outcomes. Findings suggested that (a) moderate to large effects were found on challenging behaviors and these effects were immediate; (b) the GBG was most commonly used for disruptive behavior, off-task behavior, aggression, talking out, and out-of-seat behaviors; (c) the GBG has been implemented primarily in general education elementary school settings; and (d) correct application of reward procedures are important for intervention effectiveness. Study limitations, implications for practice, and areas for future research are presented.